Oxidative stress markers are increased in patients with mastocytosis. Issue 4 (29th January 2015) - Gangemi, S.; Minciullo, P. L.; Magliacane, D.; Saitta, S.; Loffredo, S.; Saija, A.; Cristani, M.; Marone, G.; Triggiani, M.
Abstract: Background: Mastocytosis is characterized by clonal proliferation of mast cells limited to the skin (cutaneous mastocytosis: CM and mastocytosis in the skin: MIS) and/or involving internal organs (systemic mastocytosis: SM). Oxidative stress occurring in various inflammatory and neoplastic disorders causes molecular damage with the production of advanced oxidation protein products (AOPPs) and advanced glycation end products (AGEs). We evaluated these markers of oxidative stress in patients with CM/MIS and SM and correlated their levels with the presence of symptoms related to mast cell activation. Methods: Serum levels of AOPPs and AGEs in 34 patients with mastocytosis (23 CM/MIS and 11 SM) and 27 healthy controls were measured by spectrofluorimetric and spectrophotometric methods. Serum tryptase levels were measured by immunofluorescence. Results: Serum AOPPs, but not AGEs, were significantly higher in patients with mastocytosis as compared to healthy controls. While serum tryptase levels were higher in patients with SM as compared to those with CM/MIS, there was no difference in AOPP and AGE concentrations between these two groups of patients. Patients with recurrent mediator‐related symptoms had lower AOPPs and AGEs as compared to patients without symptoms. AOPPs and AGEs were inversely correlated with the severity of symptoms, and in patients with symptoms, AOPPs correlated with tryptase levels. Discussion: Our data show that mastocytosis is associated with a state of increased oxidative stress that, in patients with mediator‐related symptoms, correlates with mast cell burden as assessed by tryptase. Patients with symptoms presumably have an adaptive response resulting in lower blood levels of AOPPs and AGEs.